Multi-user Glucose Meter with Insulin Dosage Recommendation - Paglinawan, Arnold C.; Cruz, Febus Reidj; Paglinawan, Charmaine; Blas, Dorothy Faye; Daza, John Colin; Felix, Almie Anne; Chung, Wen Yaw; Sauli, Zaliman (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Diabetes (Diabetes mellitus) is a metabolic disease that occurs either when the pancreas does not produce enough insulin to regulate blood sugar or when the body itself cannot effectively use the insulin it produces, it leads to increased concentration of glucose in the blood. The most advanced glucose meter module available in the market does not have the capability to create a profile for multiple users and save the test readings they make. In this study, a glucose meter module is modified to effectively store blood glucose reading under a user’s profile for blood glucose monitoring purposes. After the reading has been completed, a pop-up window will appear which will show the user the recommended starting dose based on the weight and condition of the user. The accuracy of the device in providing glucose reading is similar to the ones available in the market since the researchers used a commercially available glucose meter modules and innovated it to do additional functions.